Incidence of Orthostatic Hypotension in Schizophrenic Patients Using Antipsychotics at Sambang Lihum Mental Health Hospital, South Kalimantan - Noor Cahaya; Sandra Putri Wijaya; Khoerul Anwar (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Schizophrenia is a psychiatric disorder that requires antipsychotics therapy. Antipsychotics cause many side effects, including orthostatic hypotension. The study aimed to describe the incidence of orthostatic hypotensive side effects experiences by schizophrenia patients at the Sambang Lihum Mental Health Hospital, South Kalimantan. This research was observational description research with data sampling by medical records. This research was conducted to 300 medical records of patients period January-December 2018 which received antipsychotics medication and data analyzed by univariate analysis. The results showed the number of patients who experienced orthostatic hypotension was 98 patients (32.67%) and no experienced were 202 patients (67.33%). Incidence of orthostatic hypotension in haloperidol 54.35% (N=46); trifluoperazine 100% (N=1); clozapine 84.62% (N=13); olanzapine 100% (N=1); haloperidol-chlorpromazine 27.27% (N=11); haloperidol-haloperidol 42.86% (N=7); clozapine-risperidone 16.67% (N=6); haloperidol-clozapine 15.05% (N=93); haloperidol-olanzapine 50% (N=2); haloperidol-risperidone 31.82% (N=22); trifluoperazine-olanzapine 100% (N=1); trifluoperazine-clozapine 22.22% (N=9); trifluoperazine-risperidone 5.56% (N=18); chlorpromazine-haloperidol-haloperidol 33.3% (N=3); chlorpromazine-haloperidol-trifluoperazine 100% (N=3); haloperidol-trifluoperazine-chlorpromazine 100% (N=1); chlorpromazine-haloperidol-clozapine 42.86% (N=7); chlorpromazine-trifluoperazine-clozapine 100% (N=1); chlorpromazine-trifluoperazine-olanzapine 100% (N=1); chlorpromazine-trifluoperazine-risperidone 50% (N=2); trifluoperazine-haloperidol-risperidone 100% (N=4); haloperidol-trifluoperazine-risperidone 100% (N=1); trifluoperazine-haloperidol-clozapine 40% (N=5); haloperidol-haloperidol-clozapine 80% (N=5); clozapine-risperidone-trifluoperazine 100% (N=4); risperidone-clozapine-haloperidol 20% (N=10). The conclusion from this study was the percentage of orthostatic hypotension on schizophrenia patients at the Sambang Lihum Mental Health Hospital was 32.67% (N=98).